"Blind" targeting in action: From phage display to breast cancer cell targeting with peptide-gold nanoconjugates. (September 2016) - Galbiati, Elisabetta; Gambini, Luca; Civitarese, Viola; Bellini, Michela; Ambrosini, Dario; Allevi, Raffaele; Avvakumova, Svetlana; Romeo, Sergio; Prosperi, Davide
Graphical abstract: Abstract: Tumor homing peptides (THPs) specific for a representative breast cancer cell line (MCF-7) were carefully selected basing on a phage-displayed peptide library freely available on the web, namely the "TumorHoPe: A Database of Tumor Homing Peptides". The selected THPs were synthesized and evaluated in terms of their affinity toward MCF-7 cells. Out of 5 tested THPs, 3 best-performing peptide sequences and 1 scrambled sequence were separately conjugated to spherical gold nanoparticles yielding stable nanoconjugates. THP nanoconjugates were examined for their ability to actively target MCF-7 cells in comparison to noncancerous 3T3-L1 fibroblast cells. These THP-gold nanoconjugates exhibited good selectivity and binding affinity by flow cytometry, and low cytotoxicity as assayed by cell death experiments. The uptake of targeted nanoconjugates by the breast cancer cells was confirmed by transmission electron microscopy analysis. This work demonstrates that it is possible to exploit the conjugation of short peptides selected from phage-displayed libraries to develop nanomaterials reliably endowed with tumor targeting potential irrespective of a specific knowledge of the target cell biology.